Program Pendampingan Pengolahan Ubi Kayu (Manihot Esculenta) Sebagai Alternatif Peningkatan Ekonomi Dalam Pemberdayaan Umat Buddha di Desa Binjai Ngagung Kec. Bekri Kabupaten Lampung Tengah - Taridi; Komang Sutawan; Sandjaya Dharmatanna; Tupari; Susanto (Jurnal Pengabdian dan Pengembangan Inovasi kepada Masyarakat (PENAMAS), 2023)
The community service activities carried out aim to contribute to Buddhism, especially for economic development. This activity was carried out in the village of Binjai Ngagung, located in Bekri District, Central Lampung Regency, Lampung Province. In its implementation, namely optimizing the processing of cassava into tiwul with modern tools so that it becomes a high-value food ingredient. The skills of Binjai Ngagung Buddhists in processing cassava into processed ingredients, especially tiwul, have increased. The number of laymen and women in that village is 120, but only 30% of the numbers make tiwul conventionally. After having training for the number of people, the people who can produce tiwul are about 60% of the 120. When we compare conventional methods and production by machines, there are strong differences. The use of machines can produce Tiwul of about 50 kg, while conventional methods only produce 5 kg.